Pengaruh Terpaan Media dan Lingkungan Sosial terhadap Perilaku Penyimpangan Seksual Remaja pada Cerita #Boyxboy di Wattpad - Agustina, Niken Ayu; Yudiningrum, Firdastin Ruthnia (Jurnal Komunikasi Massa, 2024)
This research is a quantitative research and uses the S-O-R theory. This study aims to determine the effect of media exposure (X1) and social environment (X2) on adolescent sexual deviant behavior (Y) in the #boyxboy story on Wattpad partially and simultaneously. This study was conducted with the consideration of Wattpad as a place to work and fulfill reading hobbies, but it is not only filled with useful works but also filled with inappropriate works such as the #boyxboy story. For this reason, it is hoped that this study can provide insight to be more selective in using media and choosing the right environment, as well as a consideration for the next research idea. This study uses primary data from a questionnaire distributed to 96 respondents who read the #boyxboy story with qualifications determined by the researcher according to the research topic. Data processing was carried out with the help of IBM SPSS v.29. The results of this study indicate that all hypotheses are accepted. The variables of media exposure and social environment have a positive and significant effect, both partially and simultaneously, on the variables of adolescent sexual deviant behavior in the #boyxboy story on Wattpad. The coefficient of determination test shows that variables X1 and X2 can provide an influence of 36.7% on variable Y. while the rest, which is 63.3%, is influenced by other variables not examined in this study.